2000
DOI: 10.1097/00001573-200009000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoprotein oxidation, antioxidants, and atherosclerosis

Abstract: Oxidized low density lipoproteins (LDLs) are believed to be the most atherogenic form of LDL. However, although a number of experimental data support this concept, the protective role of antioxidants that may prevent LDL oxidation in atherosclerosis is only partially confirmed by studies in humans. Observational and epidemiologic data as well as randomized trials failed to provide clear-cut indications because of mixed results on the protective role of antioxidants against cardiovascular diseases. In spite of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 90 publications
1
54
0
3
Order By: Relevance
“…Increased oxidative stress appears to play an important role in the chronic inflammatory responses to hypercholesterolemia [9]. Although the precise mechanism of atherogenesis is not fully understood, oxidative modification of LDL is considered to be an essential process in the activation of the inflammatory pathway leading to atherosclerosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress appears to play an important role in the chronic inflammatory responses to hypercholesterolemia [9]. Although the precise mechanism of atherogenesis is not fully understood, oxidative modification of LDL is considered to be an essential process in the activation of the inflammatory pathway leading to atherosclerosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that the oxidation of low-density lipoprotein cholesterol (LDL-C) plays an important part in atherogenesis, 21 and it is possible that excess circulating glucose may facilitate peroxidation of cholesterol. [22][23][24] It has also been observed that diabetes is associated with oxidative stress, 25 which is in turn associated with atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These products originated in vivo from oxidized lipoproteins and lipid membranes were linked to initiation and propagation of atherosclerosis (Zhang & Salomon, 2005;Mitra et al, 2011;Hulsmans et al, 2010). The effect of dietary oxidized fat as a contributor to the oxidative stress was also investigated by several groups including our group (Catapano et al, 2000;Drüeke et al, 2001;Garelnabi et al, 2008;Mitra et al, 2011). While there is a consensus in understanding of initial oxidative steps in the generation of early fatty streak lesions as well as the role of products of peroxidized lipid decomposition such as aldehydes in atherosclerosis, the role of further oxidation into neutral carboxylic acids is still obscure.…”
Section: Introductionmentioning
confidence: 99%